1995
DOI: 10.1016/0014-5793(95)00996-m
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the cDNA encoding a novel protein disulfide isomerase‐related protein (PDIR)

Abstract: We isolated the cDNA of a novel protein disulfide isomerase (PDI)-related protein, designated PDIR, from a human placental cDNA library. Deduced from its nucleotide sequence, PDIR has the three CXXC-like motifs (Cys-Ser-MetCys, Cys-Giy-His-Cys and Cys-Pro-His-Cys), which are found in proteins within the PDI superfamily and are responsible for oxidoreductase activity. PD|R has a hydrophobic stretch at its amino terminus, which may serve as a signal sequence, and the putative endoplasmic reticulum (ER) retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…A limited amount of ROS can be buffered in cells by glutathione and thioredoxin (54,55). This raises the possibility that the increased vulnerability of IKK␤-KM-expressing cells to Cr(VI) may be partially due to a reduced generation of oxidative buffering molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited amount of ROS can be buffered in cells by glutathione and thioredoxin (54,55). This raises the possibility that the increased vulnerability of IKK␤-KM-expressing cells to Cr(VI) may be partially due to a reduced generation of oxidative buffering molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the gene expression profiling study showed that the lowest expressed gene in IKK␤-KM cells, compared with that in IKK␤ cells, is the gene encoding proteindisulfide isomerase-related protein (Fig. 5), an important member of the thioredoxin superfamily participating in redox regulation (55). Lowered oxidative buffering could lead to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about the function of PDIR [140], its domain structure (b-a o -a-ah) is interesting. Each a-type domain has a different active-site sequence : -Cys-Ser-Met-Cys-, -CysGly-His-Cys-and -Cys-Pro-His-Cys-.…”
Section: Pdirmentioning
confidence: 99%
“…The 300-bp xh20 cDNA fragment exhibits 68.5% identity to human protein disulfide isomerase (PDI; Ref. 40) over a 178-nucleotide span covering the first thioredoxin-like domain of human PDI. Protein disulfide isomerases are multifunctional proteins; a major role is to assist in the folding of proteins containing disulfide bonds, and significantly, PDIs are also cellular T 3 binding proteins (41).…”
Section: Identification Of T 3 -Regulated Neuralmentioning
confidence: 99%